Improved Sitting Balance in Children with Cerebral Palsy: Body Functions to Activity and Participation - Akyuz, Merve; Dursun, Nigar; Gokbel, Tugba; Cekmece, Cigdem; Dursun, Erbil (Journal of Pediatric Neurology, 2022)
The aim of this study is to evaluate the changes in activity and participation domains of International Classification of Functioning (ICF), Disability and Health, in children with cerebral palsy (CP) who received integrated botulinum toxin A (BoNT-A) treatment with intensive rehabilitation with a treatment goal of improved sitting balance. In this prospective observational study, 29 patients with CP (mean age: 6.7 ± 3.8 years) and the Gross Motor Function Classification System (GMFCS) levels of IV and V were included. The primary outcome measures were the mean changes from baseline to posttreatment weeks 10 to 12 of the Child and Adolescent Scale of Participation (CASP) and Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD). The modified Ashworth scale (MAS) and Tardieu scale (TS) results at 6 to 8 weeks of posttreatment were the secondary outcome measures. Statistically significant improvements in home and community participation of CASP (p < 0.001 and 0.001), CPCHILD (p < 0.01), MAS (p < 0.001), and all parameters of TS (p < 0.05) were recorded after treatment. The result of this prospective, observational study showed that the functional improvements in sitting balance by the integrated BoNT-A treatment provides positive effects on activity and participation levels of the patient and quality of life of patients and their families.
Keywords: cerebral palsy; botulinum toxin-A; sitting balance; activity; participation